Pengaruh Kepemilikan Institusional, Konsentrasi Kepemilikan Dan Dividen Terhadap Kinerja Perusahaan - Ira Wikartika; Fajar Syaiful Akbar (Universitas Muhammadiyah Sidoarjo, 2020)
Improving company performance is crucial for the company's future life continuity. The company has a primary objective that increases the prosperity of shareholders. Basically, investors expect returns in the form of dividends. The structure of ownership and dividends is one way to improve the company's performance. This research aims to determine the influence of institutional ownership, ownership concentration, and dividends on the company's performance. The research methods used are quantitative methods using multiple linear regression analysis techniques. The research population uses companies listed on LQ45 in the Indonesia Stock Exchange. Sample research of 45 companies during the year 2018. The results showed that institutional ownership and ownership concentration did not affect the company's performance while dividends were influential in the company's performance.